2020
DOI: 10.3892/ijmm.2020.4792
|View full text |Cite
|
Sign up to set email alerts
|

CircRNAs open a new era in the study of cardiovascular disease (Review)

Abstract: Circular RNAs (circRNAs) are non-coding RNAs that are found in the cytoplasm or stored in the exosomes, where they are not affected by RNA exonucleases. CircRNAs are widely expressed in mammalian tissues and cells. A number of studies have suggested that circRNAs are associated with the physiology and pathology of cardiovascular diseases (CVDs). Therefore, circRNAs have been considered as effector molecules and biomarkers in the cardiovascular system. The present review article summarizes the biological origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 133 publications
(197 reference statements)
0
15
0
Order By: Relevance
“…Mounting evidence has shown that circRNAs have emerged as a novel special class of endogenous noncoding RNAs. To date, more and more studies have reported strong associations between circRNAs and cardiovascular disease ( Li et al, 2020 ; Zhang and Wang, 2020 ; Yu et al, 2021 ). What is more, circRNAs can regulate parent gene expression or function as miRNA sponges to affect disease initiation and progression.…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence has shown that circRNAs have emerged as a novel special class of endogenous noncoding RNAs. To date, more and more studies have reported strong associations between circRNAs and cardiovascular disease ( Li et al, 2020 ; Zhang and Wang, 2020 ; Yu et al, 2021 ). What is more, circRNAs can regulate parent gene expression or function as miRNA sponges to affect disease initiation and progression.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have found an association between exosomal circRNAs and the pathogenesis of AS. 444 , 445 Wen et al suggested that the expression of exosomal circRNA‑0006896 in circulation is positively associated with the levels of TG, LDL, and C-reactive protein (CRP) in patients with unstable plaque atherosclerosis. 445 The study also reported that the elevated circulating exosomal circRNA‑0006896 leads to high expression of circRNA‑0006896 in ECs, which results in an increases in capacities of proliferation and migration in ECs.…”
Section: The Roles Of Exosomal Ncrnas In Human Diseasesmentioning
confidence: 99%
“…It has been reported that the sorting of circRNAs to exosomes can be controlled by modulating the levels of relevant miRNAs in parental cells and can transfer bioactive substance to target cells (55). It has been confirmed that circRNAs could exert biological functions in multiple aspects, including participating in neuronal development (56) and the pathogenesis of cancer, cardiovascular, neurological, and autoimmune diseases (57)(58)(59)(60). In addition, circRNAs serve as potential biomarkers for many diseases (61), especially cancer (62).…”
Section: Exosomes and Exosomal Transcriptomesmentioning
confidence: 99%